(untitled) (Academicia Globe: Inderscience Research, 2022)
The article examines the theoretical aspects of the impact of labor migration on the growth of human capital, analyzes the current state of migration processes in the country, the causes and consequences of youth migration, based on the results obtained, appropriate conclusions are drawn on the problem under study.